2020
DOI: 10.1038/s41598-020-76570-9
|View full text |Cite
|
Sign up to set email alerts
|

Opioid agonist and antagonist use and the gut microbiota: associations among people in addiction treatment

Abstract: Murine models suggest that opioids alter the gut microbiota, which may impact opioid tolerance and psychopathology. We examined how gut microbiota characteristics related to use of opioid agonists and antagonists among people receiving outpatient addiction treatment. Patients (n = 46) collected stool samples and were grouped by use of opioid agonists (heroin, prescription opioids), antagonists (naltrexone), agonist–antagonist combinations (buprenorphine–naloxone), or neither agonists nor antagonists within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 55 publications
3
35
2
Order By: Relevance
“…Patients using opioid agonists exhibit a lower abundance of Roseburia (SCFA producer) and Bilophila (bile acid metabolizer), but there were no differences in patients using opioid antagonists. This finding parallels work in preclinical models that demonstrate drug use disrupts SCFA production and bile acid balance which are crucial reducing inflammation in the gut, and contribute to changes in drug-taking behavior (Gicquelais et al 2020).…”
Section: Opioid Use and Microbessupporting
confidence: 67%
See 1 more Smart Citation
“…Patients using opioid agonists exhibit a lower abundance of Roseburia (SCFA producer) and Bilophila (bile acid metabolizer), but there were no differences in patients using opioid antagonists. This finding parallels work in preclinical models that demonstrate drug use disrupts SCFA production and bile acid balance which are crucial reducing inflammation in the gut, and contribute to changes in drug-taking behavior (Gicquelais et al 2020).…”
Section: Opioid Use and Microbessupporting
confidence: 67%
“…Systemic inflammatory factors originating in the gut might result in central nervous system effects through a compromised blood-brain barrier caused by chronic opioid use. Similar to shifts in Roseburia and Bilophila observed by Gicquelais et al (2020) levels of SCFA's are reduced by the peripheral μ-opioid receptor agonist and anti-diarrheal agent loperamide, perhaps due to a decrease in butyrateproducing bacteria (Touw et al 2017). In the periphery, SCFAs act on GPCR's free fatty acid receptors 2 (FFAR2) and 3 (FFAR3) to regulate leucocyte functions, such as the production of eicosanoids, chemokines, and cytokines involved in inflammatory responses (Vinolo et al 2011b).…”
Section: Opioid Use and Metabolitesmentioning
confidence: 65%
“…Interestingly, the reduction of N -acyl-serotonin levels in intestinal tissues following chronic heroin administration is similar to that observed in mice following 1 week treatment with a cocktail of antibiotics ( Guida et al, 2018 ), and hence is again potentially indicative of the occurrence of opiate-induced intestinal dysbiosis. Indeed, chronic treatment with, and development of tolerance to and addiction from, opiates is now well established to be accompanied by changes in the gut microbiota composition ( Banerjee et al, 2016 ; Wang et al, 2018 ; Gicquelais et al, 2020 ; see Salavrakos et al, 2021 for review). Opiates do not need to be administered orally in order for such changes to be observed, and it has been suggested that an altered gut microbiota composition may participate in morphine addiction ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in both rodents and humans have suggested that gut microbiota might be modulated by chronic opiate use and intervene in tolerance to and dependence from opiates ( Banerjee et al, 2016 ; Kang et al, 2017 ; Wang et al, 2018 ; Acharya et al, 2017 ; Gicquelais et al, 2020 ; see Meckel and Kiraly 2019 for a review). Indeed, the gut microbiota is increasingly being suggested to play a role in behavior and its disturbances induced by psychotropics (see Cussotto et al, 2019 for a review) and to interact with eCBome signaling in both the brain and gut ( Manca et al, 2020a ; Manca et al, 2020b ; see Iannotti and Di Marzo, 2021 for review).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Roseburia is a well-known producer of Butyrate and is associated with positive health outcomes (Tamanai-Shacoori et al, 2017). In other drugs of abuse, the depletion of Roseburia is associated with increase alcohol intake (Seo et al, 2020), and decreased Roseburia may relate to increased gut permeability/inflammation and dysregulation of bile acids (Gicquelais et al, 2020). A higher abundance of butyrate producing Clostridia in the Resistant animals is also protective as depletion of Clostridia can increase aerobic expansion of opportunist microbes and increase inflammation (Rivera-Chavez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%